Analisis Faktor yang Mempengaruhi Marjin Pemasaran Biji Kopi Robusta di Kabupaten Tanggamus - Apip Gunaldi Dalimunthe; Sri Ariani Safitri; Faiz Ahmad Sibuea (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Coffee is the dominant tropical commodity in global commerce, accounting for 50% of all low-commodity exports. The worldwide allure of coffee primarily stems from its distinctive flavor and is supported by economic, social, traditional, and historical factors. This research aims to ascertain the marketing margins of robusta coffee and identify the elements that impact these margins. The investigation used the descriptive analysis approach. The study included a total of 68 farmers who were selected by random selection, as well as four merchants who were recruited using the snowball sampling method. The data analysis will then focus on an analysis of the marketing margin and a multiple linear regression analysis to identify the following factors that impact the marketing margins of robusta coffee. The study's results indicate that the first channel exhibits a highly efficient marketing channel, demonstrating a minimal marketing margin of IDR.1.520/Kg. Furthermore, the variables influencing marketing margins include the various marketing channels. The sales volume and marketing distance of coffee do not substantially impact marketing margins.